Design of A Dual-Wide Band BPF Utilizing Parallel Coupled Microstrip Lines and A Centered Arrow-Shaped Resonator - Khudaraham, Ahmed Lateef; Naji, Dhirgham Kamal (Al-Nahrain Journal for Engineering Sciences, 2020)
This paper presents a dual wide-band band pass filter (DWB-BPF) by using two parallel, symmetrical micro-strip lines loaded by a centered resonator, consisting of a T- and a triangle-shaped geometry, attached at the lower and upper ends, respectively. The filter reveals good performance and both the passbands can be independently controlled by adjusting specific parts of the filter. The proposed BPF is simulated by using CST microwave studio package and the simulated result is verified experimentally with good agreement between the two results.  The fabricated prototype BPF demonstrates two passbands located at 2.3 GHz and 6.35 GHz center frequencies with 39% and 23.6% of 3-dB fractional bandwidth (FBW), respectively and a good insertion and return losses. The designed BPF can be targeted for wireless local area network (WLAN), WIFI and satellite communication systems.